Globalisation and superstar firms - Vavoura, Charikleia (2018)
Strong empirical evidence points towards an extremely skewed distribution of exporters, corresponding to a few “superstar” firms operating alongside a fringe of small competitors. Superstars are characterised by superior efficiency, increased access to financial capital and, unlike fringe firms, by the ability to internalise the impact of their behaviour on the market. We develop a model in order to examine how productivity differences result in different abilities to invest in cost-reducing innovation which, in turn, allows firms to expand to the extent that they can exploit their market power. We then introduce international trade into this model and calculate the impact of increasing trade openness on aggregate welfare. We show that incorporating productivity heterogeneity jointly with differences in strategic behaviour generates a composition effect that dampens the pro-competitive effect of trade liberalisation. This effect materialises through a market share reallocation from smaller towards larger rivals. We find that, although trade always increases welfare by reducing the average markup and markup heterogeneity, gains from trade are lower when market power distortions are more severe. Consequently, in the presence of such distortions, size-dependent policies could have a welfare-enhancing role to play. We then use an appropriately augmented version of our model to account for the role of credit constraints differences between superstars and smaller enterprises. We examine how an economy’s financial development affects the welfare gains from trade and explore the role of large firms. We show that trade benefits less financially developed countries more and that the oligopolistic inefficiency resulting from the presence of large firms crucially alters theoretical predictions of the gains from trade. We go on to investigate the effect of trade with a more financially developed partner and find that it could act as a substitute for financial development by diminishing the impact of domestic credit market and oligopolistic inefficiencies.